(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research, The Method of Doubt between (Al-Ghazali and Descartes), interprets and explains the similarities and differences of the two philosophers on the issue of knowledge from doubt to certainty. In order to understand the truth and different dimensions of this issue, which belongs to two different worldviews and eras in the medieval Islamic and modern European world, the theses and arguments of both philosophers on doubt as the beginning and path to knowledge and certainty are discussed. This is done by highlighting their main views on their chain of reasoning, how arguments begin with the precedence of doubt until they reach the truth. Although most of their arguments are similar, but they differ in the way they get rid of doubt and reach certainty. This radical difference is that Descartes reaches certainty and truth through doubt, within rational thinking, and his Cogito (I think, Therefore I am), but Al-Ghazali in his Sufi Philosophical journey (Mysticism), he waits for the truth to be revealed to him by God (Allah) and put into his heart as a bright and illuminating light, which is a kind of enlightenment of the heart. However, despite the methodological differences between both of them in the Rational and the heart knowledge, doubt and the method of doubt for both are steps towards achieving certain knowledge beyond all doubt, to access emphatic knowledge, but each gives different status to consciousness and emotion, as well as to mind and heart. As a result, we find that the experiences of both philosophers in sustaining preconceptions and methods of arriving at truth are important and unique, even though they belong to two different philosophical and religious worldviews.